Scaling precision: Tanaashi Technologies' client-centric model enhancing Small and Medium Enterprises (SMEs) sustainability in developing economies - Aditi Singh; Ashish Bajpai (Sustainable Futures)
The study underpins the importance of businesses contributing to resource efficiency to achieve SDGs. This case examines the growth journey of Tanaashi Technologies Pvt. Ltd., an Indian start-up dedicated to SMEs in developing economies under the motto of ‘bringing resource efficiency.’ Grounded in Sustainable Development Goals (SDGs) #8, #9, #12, and #17 the study highlights Tanaashi’s client-centric approach that creates a scalable win-win model in resource-constrained environments. Through firsthand engagement with Tanaashi’s founders, management, and semi-formal client meetings, this study has uncovered how precision in problem-solving and technology-driven solutions—aligned with actual client priorities rather than speculative demands—have enabled the company to scale sustainably. The findings emphasize the strategic challenge of convincing clients to invest in long-term efficiency, reinforcing how resource optimization and tailored innovation contribute to sustainable business and economic growth. The case also explores technology adoption in Small and Medium Enterprises (SMEs) through the lens of the Information Systems (IS) Success Model. By examining real business challenges, and strategic decisions this case provides valuable insights for entrepreneurs navigating similar markets, offering a practical blueprint for sustaining tech-driven enterprises in developing economies.